2013
DOI: 10.1186/2193-1801-2-318
|View full text |Cite
|
Sign up to set email alerts
|

Controlled root targeted delivery of fertilizer using an ionically crosslinked carboxymethyl cellulose hydrogel matrix

Abstract: AimsThe recent increases in food prices caused by the corresponding increases in fertilizer costs have highlighted the demand for reducing the overuse of fertilizers in industrial agriculture. There has been increasing interest in developing plant root-targeted delivery (RTD) of fertilizers in order to address the problem of inefficient fertilizer use. The aim of this study is to develop a low cost controlled release device to deliver fertilizers to plant roots and thereby increase fertilizer use efficiency.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 22 publications
1
51
0
1
Order By: Relevance
“…It has been reported that calcium ions can drastically decrease the swelling capacity for a hydrolyzed starch-and polyacrylonitrilegrafted copolymer, due to the complexing ability of the carboxylate groups, inducing the formation of intra-and intermolecular complexes [140,141]. Then, depending on the chemically SH network, significant effect is observed on absorption capacity of water, and consequently, on the adsorption capacity of agricultural nutrients [142]. Cations from saline solutions compete with nutrient ions by the active sites inside the 3D hydrogel structure [137].…”
Section: Effect Of Ionic Strengthmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that calcium ions can drastically decrease the swelling capacity for a hydrolyzed starch-and polyacrylonitrilegrafted copolymer, due to the complexing ability of the carboxylate groups, inducing the formation of intra-and intermolecular complexes [140,141]. Then, depending on the chemically SH network, significant effect is observed on absorption capacity of water, and consequently, on the adsorption capacity of agricultural nutrients [142]. Cations from saline solutions compete with nutrient ions by the active sites inside the 3D hydrogel structure [137].…”
Section: Effect Of Ionic Strengthmentioning
confidence: 99%
“…Controlled nutrient release from biodegradable chemical hydrogels have been widely studied all over the world [108,133,135,142,144,145]. Controlled nutrient release from polysaccharide-based SH, as carriers, improved the functional efficiency of nutrients, herbicides, insecticides and fungicides, decreasing the cost of the application process, toxicity for humans and environmental pollution [144].…”
Section: Controlled Nutrient Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Naturally it is fully water soluble and usually does not form a hydrogel. CMC, however, has the capacity to form hydrogels by ionic interaction with multivalent cations such as iron (III) and calcium (Yakup Anca 2000;Davidson et al 2013). Additionally CMC (Rokhade et al 2006), divinyl sulfone (Sannino et al 2004), and diepoxies (Kono et al 2013), as well as with interaction with radiation (Wach et al 2001) and other methods.…”
Section: Ether Conjugationmentioning
confidence: 97%
“…has reported hydroxyethyl cellulose cross‐linked with borax as a matrix for the slow delivery of urea and liquid NP fertilizers. Davidson et al . reported the development of a controlled root targeted delivery fertilizer using ionically cross‐linked carboxymethyl cellulose hydrogel matrix with increased fertilizer use efficiency.…”
Section: Introductionmentioning
confidence: 99%